2022
DOI: 10.32604/ijmhp.2022.019177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of College Students’ Perceived Stress on Anxiety in the Time of COVID-19: The Chain Mediation Role of Psychological Resilience and Regulatory Emotional Self-Efficacy

Abstract: COVID-19 has changed the way of learning and life of college students. The purpose is to explore the relationship between perceived stress and anxiety, and the mediating effect of resilience and regulatory emotional self-efficacy in college students during COVID-19. 309 students from three colleges were selected as research participants (average age 19.79 ± 1.11 years). SPSS was used to measure the correlation between variables. Amos was used to test the path coefficient and mediating effect of the hypothetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…This result also confirms the previous findings that there is a close connection between an individual's confidence in their own abilities and the evaluations of others (Caprara and Steca, 2006). Meanwhile, regulatory emotional self-efficacy is effective in alleviating negative emotions and restoring confidence (Li and Xie, 2021), thus perceiving more positive emotions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result also confirms the previous findings that there is a close connection between an individual's confidence in their own abilities and the evaluations of others (Caprara and Steca, 2006). Meanwhile, regulatory emotional self-efficacy is effective in alleviating negative emotions and restoring confidence (Li and Xie, 2021), thus perceiving more positive emotions.…”
Section: Discussionsupporting
confidence: 90%
“…Regulatory emotional self-efficacy pertains to an individual's belief or level of confidence in effectively managing and regulating one's own emotions, and it mainly consists of perceptions of one's own different emotional states, the individual's understanding of other people's emotions, one's ability to manage emotions, and the corresponding different emotional responses (Caprara et al, 2008), involving two dimensions: ameliorating negative emotions and expressing positive emotions (Bandura et al, 2003). Previous research has demonstrated that regulatory emotional self-efficacy is a negative predictor of negative emotions such as depression and anxiety, generating higher subjective well-being (Pu et al, 2017;Li et al, 2020b;Li and Xie, 2021;Xiao and Huang, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additional researchers have indicated that self-efficacy can influence levels of anxiety through the following mechanisms. Individuals with high self-efficacy exhibit greater confidence in confronting obstacles and demands, enabling them to effectively manage anxious feelings and, therefore, diminish anxiety levels ( Li and Xie, 2022 ). Furthermore, engaging in physical exercise, as a form of proactive action, can bolster personal self-efficacy, boost self-assurance, and foster enduring psychological resilience, thus aiding in the resistance to anxiety-inducing disruptions ( Yang et al, 2023 ).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…It accentuates the cognitive, emotional, and behavioral processes contributing to an individual's capacity to overcome obstacles, maintain mental health, and foster a positive development (He et al 2013). Psychological resilience includes emotional regulation, self-efficacy, optimism, adaptive coping strategies, and utilizing personal strengths and resources (Li and Xie 2022;Süss and Ehlert 2020).…”
Section: Psychological Resilience and Mental Healthmentioning
confidence: 99%